Алгебра. Базовый курс с решениями и указаниями: учебно-методическое пособие - Золотарева Н. Д. Наталья Дмитриевна; Попов Ю. А. Юрий Александрович; Семендяева Н. Л. Наталья Леонидовна; Федотов М. В. Михаил Валентинович (ВМК МГУ - школе)
ЕГЭ. Олимпиады. Экзамены в ВУЗ